'I Can't Meet That Deadline': Implications of New Truck Driver Hours of Service Regulations for Florida Agriculture - Richard Beilock (EDIS)
In 1939, the U.S. Federal Government established regulations limiting the number of hours that truck drivers could drive and be on duty. These are known as Hours of Service Regulations (HOSR). In response to concerns about fatigue-related accidents, the U.S. Congress mandated studies in 1995 to determine how HOSR could be improved. Eight years, many millions of dollars, and over 53,000 public comments later the revised HOSR came into effect on January 4, 2004. Over 99% of all Florida produce and ornamentals shipped outside of the state are delivered by truck. Rapid and reliable transport for these highly valued perishables is essential. In this paper, the revised HOSR is described and some assessments are made of its effect on trucking. This is EDIS document, FE542, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.